Glucosylceramides From Lomentospora prolificans Induce a Differential Production of Cytokines and Increases the Microbicidal Activity of Macrophages - Xisto, Mariana Ingrid Dutra da Silva; Henao, Julián Esteban Muñoz; Dias, Lucas dos Santos; Santos, Giulia Maria Pires; Calixto, Renata de Oliveira Rocha; Bernardino, Mariana Collodetti; Taborda, Carlos Pelleschi; Barreto-Bergter, Eliana (Frontiers in Microbiology, 2019)
Lomentospora prolificans is an emerging opportunistic fungus with a high resistance to antifungal agents and it can cause localized infections in immunocompetent patients and disseminated infections with a high mortality rate in immunosuppressed patients. Glucosylceramides (GlcCer) are the main neutral glycosphingolipids expressed in fungal pathogens. They are bioactive molecules presenting different functions, such as involvement in fungal growth and morphological transitions in several fungi. The elucidation of the primary structure of the fungal surface glycoconjugates could contribute for the understanding of the mechanisms of pathogenicity. In this work, GlcCer species were isolated from mycelium and conidia forms of L. prolificans and their chemical structures were elucidated by mass spectrometry (ESI-MS). GlcCer purified from both forms presented a major species at m/z 750 that corresponds to N-2-hydroxyhexadecanoyl-1-β-D-glucopyranosyl-9-methyl-4,8-sphingadienine. Monoclonal antibodies against GlcCer could recognize L. prolificans GlcCer species from mycelium and conidia, suggesting a conserved epitope in fungal GlcCer. In addition, in vivo assays showed that purified GlcCer species from both forms was able to induce a high secretion of pro-inflammatory cytokines by splenocytes. GlcCer species also promote the recruitment of polymorphonuclear, eosinophils, small peritoneal macrophage (SPM) and mononuclear cells to the peritoneal cavity. GlcCer species were also able to induce the oxidative burst by peritoneal macrophages with NO and superoxide radicals production, and to increase the killing of L. prolificans conidia by peritoneal macrophages. These results indicate that GlcCer species from L. prolificans are a potent immune response activator.